Inhibition of dual leucine zipper kinase prevents chemotherapy-induced peripheral neuropathy and cognitive impairments. Issue 10 (October 2021) - Ma, Jiacheng; Goodwani, Sunil; Acton, Paul J.; Buggia-Prevot, Virginie; Kesler, Shelli R.; Jamal, Imran; Mahant, Iteeben D.; Liu, Zhen; Mseeh, Faika; Roth, Bruce L.; Chakraborty, Chaitali; Peng, Bo; et al.
Abstract : Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) and chemotherapy-induced cognitive impairments (CICI) are common, often severe neurotoxic side effects of cancer treatment that greatly reduce quality of life of cancer patients and survivors. Currently, there are no Food and Drug Administration-approved agents for the prevention or curative treatment of CIPN or CICI. The dual leucine zipper kinase (DLK) is a key mediator of axonal degeneration that is localized to axons and coordinates the neuronal response to injury. We developed a novel brain-penetrant DLK inhibitor, IACS′8287, which demonstrates potent and highly selective inhibition of DLK in vitro and in vivo. Coadministration of IACS′8287 with the platinum derivative cisplatin prevents mechanical allodynia, loss of intraepidermal nerve fibers in the hind paws, cognitive deficits, and impairments in brain connectivity in mice, all without interfering with the antitumor activity of cisplatin. The protective effects of IACS′8287 are associated with preservation of mitochondrial function in dorsal root ganglion neurons and in brain synaptosomes. In addition, RNA sequencing analysis of dorsal root ganglia reveals modulation of genes involved in neuronal activity and markers for immune cell infiltration by DLK inhibition. These data indicate that CIPN and CICI require DLK signaling in mice, and DLK inhibitors could become an attractive treatment in the clinic when coadministered with cisplatin, and potentially other chemotherapeutic agents, to prevent neurotoxicities as a result of cancer treatment. Abstract : Supplemental Digital Content is Available in the Text. Dual leucine zipper kinase inhibition is a promising therapeutic strategy against chemotherapy-induced neurotoxicities including chemotherapy-induced peripheral neuropathy and chemotherapy-induced cognitive impairments.